PELAKSANAAN PERATURAN DAERAH KABUPATEN LOMBOK TENGAH NOMOR 14 TAHUN 2010 TENTANG PAJAK DAERAH DALAM INTENSIFIKASI PAJAK DAERAH - Hafizatul Ulum (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
Along with the passing Autonomous Region, shifted the paradigm of the organization that is giving autonomy broadest possible as stipulated in Law No. 32 the Year 2004 on Regional Government, policy change setting regional government are aligned with changes in policy towards Taxes and Levies as a foundation for regions in mobilizing the potential of local revenue, especially PAD, namely Law No. 28 the year 2009 on regional Taxes and Levies Settings local Taxes in Indonesia rooted in the constitution namely State Constitution RI 1945 Article 23A then specifically regulated in the Act number 28 the Year 2009 on regional Taxes and Levies Daerah. Pengaturan local Taxes in Central Lombok and East Lombok as a follow-up of implementation UU regulation No. 28/2009 then ditapkanlah areas: Central Lombok District Regulation No. 14 the Year 2010 on regional Taxes; East Lombok District Regulation No. 10 the Year 2010 on Regional Taxes; and East Lombok District Regulation No. 17 of 2010 Concerning Tax on Acquisition of Land and Buildings. But between East Lombok District Regulation regarding Entertainment Tax Section 21 Subparagraph (e) by Act No. 28 of 2009 Article 45 Paragraph (3) there is a conflict of norms. Comparison of Implementation of Tax Collection Areas In Central Lombok and East Lombok, Central Lombok District revenues are Tax terrain is not intensive because it does not meet the target of tax revenue, As with the East Lombok district revenues are Tax terrain is already intensively as between the target and actual tax revenue is appropriate